SISTEM INFORMASI PEMETAAN KANTOR PEMERINTAH KABUPATEN SITUBONDO BERBASIS WEB - M. Ali Mudhari (Department of Science and Technology Ibrahimy University, 2018)
Government Services is one of the supporting elements of the implementation of regional autonomy authorities in various fields in the context of carrying out the tasks of government decentralization which has the function of providing public services needed by the community, starting from services in the form of regulation or other services to meet the needs of the community in the fields of education, health and the other. One city that has many government offices and is spread in various regions in the city of Situbondo, where the city is experiencing developments in various fields, especially in the field of community service. One solution to help Situbondo residents obtain information about the geographical location and services of government offices so that it needs to be designed mapping of the Geographic Information System of the Situbondo Regency Government Office. With this system, it is expected to provide geographical location information, office services, information services, and office agendas. In making this system, researchers used the methodology for developing a waterfall system, with several stages carried out starting from Requirements to Maintenance. The results of this study are expected to overcome the problems faced by the Situbondo district government office.